1993
DOI: 10.1007/bf00195396
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pause between spider courtship vibrations and general problems using synthetic stimuli in behavioural studies

Abstract: Abstract. Effectiveness of natural stimuli (recorded and replayed male vibratory courtship signals) in eliciting a female's vibratory response was compared with that of synthetic stimuli in a plant-dwelling spider (Cupiennius salei). Specifically, the role of interseries (pauses between consecutive male series) was evaluated. Effectiveness was assessed by the number of responding females and the number of responses per female per stimulus. In case of both synthetic and natural stimuli, effectiveness increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…The male signal's effectiveness in eliciting the female response increases with increasing duration of the interseries (Schmitt et al 1993). Since the repetition rate (number of responses, min-a) of the female is temperature dependent the maximum number of female responses per min is determined by the ambient temperature as well.…”
Section: Duration Of Interseriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The male signal's effectiveness in eliciting the female response increases with increasing duration of the interseries (Schmitt et al 1993). Since the repetition rate (number of responses, min-a) of the female is temperature dependent the maximum number of female responses per min is determined by the ambient temperature as well.…”
Section: Duration Of Interseriesmentioning
confidence: 99%
“…Since the repetition rate (number of responses, min-a) of the female is temperature dependent the maximum number of female responses per min is determined by the ambient temperature as well. For C. salei it is about 2 at 20~ It is therefore reasonable that with increasing duration of the interseries (decreasing the repetition rate of the interseries) the effectiveness of the female response increases as well, if it is calculated as the relative number of responses of a particular female to the number of male signals (Schmitt et al 1993).…”
Section: Duration Of Interseriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioural significance of this reciprocal vibratory communication over distances of up to at least 3.8 m (Schmitt et al 1993 for C. coccineus) is to ensure mutual location and appeasement of the mates. It is also important for species recognition by the female, which responds preferentially to signals of conspecific males (Barth and Schmitt 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural studies with C. salei have shown that the opisthosomal signals (and not, however, the pedipalpal signals) are necessary and sufficient to elicit the female's response (Schiich and Barth 1990). The probability of a female's response is determined by the main frequencyJ of the syllables, the temporal structure of the series and the pause duration between consecutive series (Schiich and Barth 1990;Schmitt et al 1993Schmitt et al , 1994.…”
Section: Introductionmentioning
confidence: 99%